OP0163 Treatment-Naïve, Early Rheumatoid Arthritis Patients Demonstrate Vascular and Myocardial Abnormalities on Cardiac MRI. (9th June 2015) - Erhayiem, B.; McDiarmid, A.; Swoboda, P.; Kidambi, A.; Ripley, D.; Musa, T.A.; Dobson, L.E.; Garg, P.; Horton, S.C.; Dumitru, R.B.; Andrews, J.; Greenwood, J.; et al.
Abstract : Background: Cardiac studies of patients with rheumatoid arthritis (RA) have demonstrated abnormalities in left ventricular (LV) remodelling that is associated with development of heart failure and cardiovascular (CV) morbidity and mortality 1, 2 . No studies to date have evaluated for changes in myocardial and vascular function in treatment-naïve early RA (ERA). Objectives: To evaluate whether patients with newly diagnosed, treatment-naïve ERA demonstrate myocardial and vascular changes on cardiac MRI (CMR) compared with matched controls. Methods: Sixty-six ERA patients fulfilling ACR/EULAR classification criteria and with no CVD history underwent 3.0T CMR (Philips Achieva TX) at a cardiology-CMR unit. All patients had symptoms for less than 1 year, were DMARD treatment-naïve and with minimum disease activity score (DAS28) ≥3.2. Thirty healthy controls (HC) were matched by age, sex and blood pressure. Standard balanced steady state free precession cine images were acquired and LV dimensions calculated. For aortic distensibility, multi-phase SSFP cine images (50 phases) were acquired in a plane transverse to the ascending aorta at the level of the pulmonary artery bifurcation. Aortic contours were drawn by manual planimetry of the endovascular–blood pool interface at the times of minimal and maximal distension. Additional parameters measured include strain analysis and extracellular volume (results awaited). Body surface area (BSA) index values are presented. Results: Patients in ERA and HC groups were similar mean (SD) age [49.4 (13.08) and 46.7 (11.4) respectively, p=0.33] and systolic BP [122 (23) and 126 (16) respectively, p=0.18]. Mean (SD) BSA was lower in the ERA group vs HC [(1.83 (0.22) vs 1.9 (0.21) respectively, p=0.09]. In the ERA group, median (IQR) ESR, CRP and mean (SD) DAS28 were 39.5 (28.7)mm/hr, 18.9 (27.1)mg/L and 5.65 (1.6) respectively. 54 (82%) and 48 (73%) patients were ACPA and RF positive respectively. Table 1 details CMR parameters. Aortic distensibility was significantly reduced in ERA patients compared to HC (median ± IQR, 3.19±2.16 10 -3 mmHg -1 versus 4.4±2.1 10 -3 mmHg -1, p=0.001). Other measures of arterial stiffness including aortic stiffness index, compliance and strain showed similar significant differences. Left ventricular and right ventricular end-systolic and end-diastolic volumes were all significantly lower in the ERA vs HC. A trend for lower LVmass index in the ERA group was observed and seemed to be associated with seropositivity (see table 2). Evidence for overt inflammation/fibrosis was seen in 4 patients with focal non-ischaemic patterns of LGE. Conclusions: This first CMR study in treatment-naive ERA demonstrates abnormalities at the earliest stage of RA. Reduced vascular function, ventricular volumes, and trend change in LV geometry suggest an early cardiomyopathy. This might imply higher risk for CV morbidity and mortality at time of diagnosis. Further investigation will clarify the natural history, clinical implications and the scope to modify outcome with effective RA therapy. References: Giles JT, et al. Arthritis Rheum 2010 2. Myasoedova E, et al. Arthritis Rheum 2013 Disclosure of Interest: None declared